2019
DOI: 10.1002/ejoc.201901161
|View full text |Cite
|
Sign up to set email alerts
|

Naphtho[1,2‐b:5,6‐b′]dithiophene Building Blocks and their Complexation with Cyclobis(paraquat‐p‐phenylene)

Abstract: The synthesis and characterization of 2,7-bis-(hydroxymethyl)naphtho[1,2-b:5,6-b′]dithiophene 1 is described. Electrochemical investigations revealed that 1 and its precursor naphtho[1,2-b:5,6-b′]dithiophene (NDT) are moderate π-electron donors. It was found that both compounds can form 1:1 complexes with the π-electron accepting cyclophane cyclobis(paraquat-p-phenylene) (CBPQT 4+ ). UV/Vis spectroscopy was used to determine the binding constants (K a ) associated with the complexation process leading to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…The protons associated with the numerous different SC H 3 groups attached to the TTF and MPTTF units were all observed to be shifted downfield from δ =2.30–2.70 ppm in the unoxidized 1 4+ to δ =2.85–3.05 ppm in the oxidized sample of 1 4+ . Previous investigations have shown that this behavior is entirely consistent with formation of the TTF 2+ and MPTTF 2+ dications, and therefore, of the tetra‐oxidized [2]rotaxane 1 8+ . Likewise, the protons associated with the MPTTF 2+ unit (i.e., the pyrrole‐ H protons) are shifted downfield ( δ =8.07 and 7.99 ppm in 1 8+ , Figure S2) compared to unoxidized 1 4+ ( δ =6.17–6.61 ppm), an observation that is completely consistent with the formation of a non‐complexed MPTTF 2+ dication.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The protons associated with the numerous different SC H 3 groups attached to the TTF and MPTTF units were all observed to be shifted downfield from δ =2.30–2.70 ppm in the unoxidized 1 4+ to δ =2.85–3.05 ppm in the oxidized sample of 1 4+ . Previous investigations have shown that this behavior is entirely consistent with formation of the TTF 2+ and MPTTF 2+ dications, and therefore, of the tetra‐oxidized [2]rotaxane 1 8+ . Likewise, the protons associated with the MPTTF 2+ unit (i.e., the pyrrole‐ H protons) are shifted downfield ( δ =8.07 and 7.99 ppm in 1 8+ , Figure S2) compared to unoxidized 1 4+ ( δ =6.17–6.61 ppm), an observation that is completely consistent with the formation of a non‐complexed MPTTF 2+ dication.…”
Section: Resultssupporting
confidence: 77%
“…Previous investigations [12b, 29] have shown that this behavior is entirely consistent with formationo ft he TTF 2 + and MPTTF 2 + dications, and therefore, of the tetra-oxidized [2]rotaxane 1 8 + . [30] Likewise, the protons associatedw ith the MPTTF 2 + unit (i.e.,t he pyrrole-H protons) are shiftedd ownfield (d = 8.07 and 7.99 ppm in 1 8 + ,F igure S2) comparedt ou noxidized 1 4 + (d = 6.17-6.61 ppm), an observation that is completely consistent with the formation of an on-complexed MPTTF 2 + dication.…”
Section: Chemical Oxidation Of 1 4 + +mentioning
confidence: 99%
“…The two solvent choices present distinctively different molecular environments to compare crystallization within a theoretical framework: Toluene can be viewed as an effective (good) solvent given favorable noncovalent intermolecular interactions among the aromatic cores of toluene and NDT, while hexane can be viewed as a nonfavorable (poor) solvent given the aliphatic nature of the solvent that may introduce an additional driving force for phase separation. 11 We note that toluene has been used to dissolve NDT-based crystals, 48 whereas hexane has been used as a recrystallization solvent to grow NDT crystals. 46…”
Section: ■ Introductionmentioning
confidence: 99%